Nutritional Value of Poultry Manure Fermented by Using Eubiotic with Different Levels and Times - Rizki Eka Puteri; Rani Ria Rizki; Raudhatus Saadah (Universitas Muhammadiyah Palembang, 2026)
ABSTRACT Feed prices remain a major issue in catfish farming due to the continued reliance on imported raw materials, such as fish meal, as the primary source of protein. Efforts are needed to reduce dependence on imported materials with alternative protein sources that are sustainable, economical, and offer good nutritional value. One example of utilizing waste as an alternative raw material for fish feed is chicken manure. Manure is a waste product from broiler and layer chicken farms. However, it still faces challenges, such as its relatively high crude fiber content, making it difficult to apply because it can result in low feed digestibility. Therefore, technology is needed to reduce the crude fiber content in chicken manure so that the material can be utilized optimally. This study aims to determine the appropriate dosage and fermentation time to improve the nutritional quality of chicken manure. This study used the Factorial RAL method with two factors and three replications. The first factor was the eubiotic dosage (0%, 10%, 20%), and the second factor was the fermentation time (0 days, 3 days, 6 days). The results showed a significant interaction between the eubiotic dosage and fermentation time on the percentage of crude protein, crude fiber, and cellulose. The eubiotic dosage significantly affected crude protein, crude fiber, and cellulose. Fermentation time also significantly impacts crude protein, crude fiber, and cellulose. The combination of 20% eubiotic treatment with a 6-day fermentation period was most effective in reducing crude fiber and increasing crude protein in chicken diets